PENGARUH SERVICE QUALITY DAN SUKU BUNGA TERHADAP CUSTOMER LOYALTY PT. BPR SATYA MITRA ANDALAN - SELLY SAFITRI; SUHARDI . (JURNAL ILMIAH MAKSITEK, 2020)
The need for capital to develop a business is growing rapidly, and it brings very tight competition to business people. Thisencourages the emergence of many new types of businesses that can become one of the threats for PT. BPR Satya MitraAndalan. PT. BPR Satya Mitra Andalan is one of the companies engaged in banking which has been established since 2017in the city of Batam. The purpose of this study was to determine whether there is an effect between service quality andinterest rates partially and simultaneously on customer loyalty deposits at PT. BPR Satya Mitra Andalan. In this study, theauthors used a descriptive quantitative research method using 180 populations. The population was reduced to 124populations using the slovin formula. In this study, the authors use SPSS (Statistical Product and Service Solution) version25 is a program used by the author to process data obtained from respondents. The results in this study indicate that there isa positive and significant effect between service quality and interest rates partially and simultaneously on the customerloyalty of PT. BPR Satya Mitra Andalan.